2020
DOI: 10.1371/journal.pntd.0008519
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological distribution of Echinococcus granulosus s.l. infection in human and domestic animal hosts in European Mediterranean and Balkan countries: A systematic review

Abstract: Cystic echinococcosis (CE) is a neglected zoonosis caused by infection with the cestode Echinococcus granulosus sensu lato. We carried out a systematic literature review on E. granulosus s.l. human and animal (cattle, sheep, dog) infection in European Mediterranean and Balkan countries in 2000-2019, to provide a picture of its recent epidemiology in this endemic area. MEDLINE, EMBASE, Scopus, Google Scholar and Open Grey databases were searched. Included cases were: i) for humans, data from hospital records an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 68 publications
2
51
1
Order By: Relevance
“…The findings of the present study allow for an improved understanding of the impact of CE in the study area, laying the foundations for an evidence-based decision-making process on the measures to control this disease. The analysis of the HDRs showed an estimated incidence rate in the human population of 0.4/100,000 people per year, which is in line with what already reported for northern Italy and for other hypo-endemic regions in wealthy and industrialized economies [ 7 , 9 , 25 ]. More importantly, our findings suggested that the source of the infection for most of the human cases is external to the study area, although few cases were possibly autochthonous.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The findings of the present study allow for an improved understanding of the impact of CE in the study area, laying the foundations for an evidence-based decision-making process on the measures to control this disease. The analysis of the HDRs showed an estimated incidence rate in the human population of 0.4/100,000 people per year, which is in line with what already reported for northern Italy and for other hypo-endemic regions in wealthy and industrialized economies [ 7 , 9 , 25 ]. More importantly, our findings suggested that the source of the infection for most of the human cases is external to the study area, although few cases were possibly autochthonous.…”
Section: Discussionsupporting
confidence: 88%
“…In Spain, an overall economic impact of about 150 million € was estimated in 2005 [ 33 ], meaning a monetary estimation 300 times higher than that obtained in the present study. This difference depends on the different size of the considered study areas (about 43 million inhabitants in Spain in 2005 vs 5 million in Veneto) and can be partly due to the higher incidence of hospitalized human CE cases recorded in most regions of Spain [ 7 ], compared to Veneto. Besides, this study included different costs (reduction in carcass weight, reduction in milk production and decrease in fecundity) associated to four domestic species (sheep, goats, cattle, pigs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lifecycle of echinococcosis, biologically perpetuate when dogs are fed on raw organs of infected domestic ungulates and dog remain asymptomatic but contain residual worm burden [ 22 ]. Epidemiological evidence, verify that humans are dead-end intermediate hosts and acquire infection through inadvertent consumption of eggs shed by the dogs or by physical contact with them [ 23 ].CE constitutes a rising public health threat, with average annual incidence in humans estimated to be as high as 7.74 cases/100,000 population in different countries, around the world [ 24 ]. High CE infection in humans is circumstantially linked to environmental dissemination of eggs on various matrices and surfaces by infected dogs [ 25 ].…”
Section: Life Cycle Of Some Parasites From Raw Meat Feeding Involving Pets and Humansmentioning
confidence: 99%
“…E. granulosus causes an accidental human infection; adult tapeworms are found in the intestines of canines (dog, wolf); the larval cyst stage is present in the viscera of herbivores (sheep, cattle, horse, deer, pig, camel) (King 2005). Transmission to human occurs via the fecal-oral route (Tamarozzi et al 2020).…”
Section: Introductionmentioning
confidence: 99%